Mechanobiology of mesenchymal stem cells: Perspective into mechanical induction of MSC fate. (1st July 2015) - Hao, Jin; Zhang, Yueling; Jing, Dian; Shen, Yu; Tang, Ge; Huang, Shishu; Zhao, Zhihe
Graphical abstract: Abstract: Bone marrow-derived mesenchymal stem and stromal cells (MSCs) are promising candidates for cell-based therapies in diverse conditions including tissue engineering. Advancement of these therapies relies on the ability to direct MSCs toward specific cell phenotypes. Despite identification of applied forces that affect self-maintenance, proliferation, and differentiation of MSCs, mechanisms underlying the integration of mechanically induced signaling cascades and interpretation of mechanical signals by MSCs remain elusive. During the past decade, many researchers have demonstrated that external applied forces can activate osteogenic signaling pathways in MSCs, including Wnt, Ror2, and Runx2. Besides, recent advances have highlighted the critical role of internal forces due to cell–matrix interaction in MSC function. These internal forces can be achieved by the materials that cells reside in through its mechanical properties, such as rigidity, topography, degradability, and substrate patterning. MSCs can generate contractile forces to sense these mechanical properties and thereby perceive mechanical information that directs broad aspects of MSC functions, including lineage commitment. Although many signaling pathways have been elucidated in material-induced lineage specification of MSCs, discovering the mechanisms by which MSCs respond to such cell-generated forces is still challenging because of the highly intricate signaling milieu present in MSC environment. However, bioengineers are bridging this gap by developing platforms to control mechanical cues with improved throughput and precision, thereby enabling further investigation of mechanically induced MSC functions. In this review, we discuss the most recent advances that how applied forces and cell-generated forces may be engineered to determine MSC fate, and overview a subset of the operative signal transduction mechanisms and experimental platforms that have emerged in MSC mechanobiology research. Our main goal is to provide an up-to-date view of MSC mechanobiology that is relevant to both mechanical loading and mechanical properties of the environment, and introduce these emerging platforms for tissue engineering use.